Papyrus : the plant that changed the world, from ancient egypt to today's water war - Gaudet, John J,
Offers an examination of the papyrus plant, looking at the important role it played in ancient Egyptian culture as a source of paper, as well as its unique properties that could help combat ecological and social problems in the modern world.